A collaborative supply chain management: Part 2 – the hybrid KB/gap analysis system for planning stage - Mohamed Udin, Zulkifli; Khan, Mohammad K.; Zairi, Mohamed (Emerald Group Publishing Limited, 2006)
Purpose– The intention of this paper is to promote the model of knowledge‐based collaborative supply chain management (KBCSCM) system as an alternative strategy for organisations to resolve the problems in their current supply chain management (SCM) in the era of collaborative commerce (c‐commerce). Design/methodology/approach– This paper covers the explanation of the KBCSCM system and the utilisation of the GAP analysis technique, which is embedded in the knowledge‐based system (KBS). Through this technique, the missing prerequisites of current organisations' position can be identified before implementation of some improvement programs.Findings– This paper has described a hybrid KB/GAP analysis CSCM system for application in organisations, specifically for manufacturing environment. The valid, practical and consistent solutions that are provided by KBCSCM system would assist organisations in implementing CSCM as a strategy.Research limitations/implications– Future research could consider larger sample sizes and cover other industry types which include services industry. Practical implications– The participants or players in supply chain will be able to measure their current capability in order to develop collaboration amongst them.Originality/value – This paper highlighted the utilisation of KB approach in the SCM environment. A systematic planning of CSCM has not been developed before and the development of the KBCSCM system is believed to be crucial in order to improve the competitiveness of the organisation's SCM by assisting users to easily understand the position of their organisation.